Упровадження інформаційно-комунікаційних технологій у самостійну фізкультурно-оздоровчу діяльність студентів - Кузнєцова, О; Мосейчук, Юрій (Науковий часопис Національного педагогічного університету імені М.П.Драгоманова, 2019)
В статті розкрито умови упровадження інформаційно-комунікаційних технологій у самостійну фізкультурнооздоровчу діяльність студентів. Аналіз наукових праць фахівців галузі довів, що актуальність розвитку інформаційнокомунікаційних технологій у процесі фізичного виховання студентів на сьогодні є беззаперечною. Застосування педагогічних технологій у самостійній фізкультурно-оздоровчій діяльності студентів дозволило вирішити ряд важливих і складних завдань: за допомогою електронної корпоративної пошти здійснювати систематичне листування та консультацію студентів, реалізувати контроль за підготовкою завдань самостійної роботи; простежити динаміку стану здоров’я і фізичної працездатності протягом певного періоду; сформувати систему корекційних та реабілітаційних заходів щодо збереження здоров’я і створення оптимальних умов для реалізації поставлених цілей; підготувати необхідні дидактичні матеріали для впровадження в освітній процес; реалізувати тестовий контроль за допомогою комп’ютерних програм та систематизованого електронного каталогу літератури з метою оцінювання теоретичних знань студентів.
Implementation of information and communication technologies into the students’ independent physical and health-improving activities
The article describes the conditions for the introduction of information and communication technologies into the students’ independent physical and health-improving activities. The analysis of scientific works proves that the actuality of the development of information and communication technologies in the process of students’ physical education is unconditional. The purpose of the research work is to reveal the possibilities of using information and communication technologies into the students’ independent physical and health-improving activities. In the process of implementation of the methodical system of applying health-improving technologies in students’ physical education, information and communication technologies are represented by multimedia technologies and Internet system. The main areas of the research work are to familiarize students with the main university domain and its sites, virtual excursions to the university, registration and formation of basic skills of independent work in the Moodle system, use of the information database of the level of students’ somatic health and author's computer programs, familiarization with the possibilities of electronic university libraries, deepening of the skills of work with search systems, library catalogs and the teacher’s corporate post, etc. The use of pedagogical technologies in students’ independent physical and health-improving activities allows to solve such important and complicated tasks: to conduct systematic correspondence and consultation of students through electronic corporate mail, to control the preparation of tasks for independent work; to trace the dynamics of health and physical capacity during a certain period; to form a system of correctional and rehabilitation measures to preserve health and create optimal conditions for realization of the set goals; to prepare the necessary didactic materials for implementation in the educational process; to implement test control with the help of computer programs and a systematic electronic catalog of literature in order to assess the students' theoretical knowledge.
Keywords: заклад вищої освіти, студенти, процес фізичного виховання, самостійна робота, інформаційнокомунікаційні технології.; institution of higher education, students, process of physical education, independent work, information and communication technologies.